Quando a pauta é representação, vale mais identidades ou empreendedorismo de si? uma análise de youtubers negro(a/e)s brasileiro(a/e)s - Anjos, Ana Carolina Costa dos (2021)
In the context of the Internet, after the 2010, subjects act as their own entrepreneurs on digital platforms. Terms such as representation and identity start to be appropriated and re-signified in the processes of consumption and production of digital content. Although in smaller numbers, people racialized as black consume and produce in this space of representation and do so, sometimes, undertaking their black identities. At the interface of Digital Sociology, Sociology of Racial and Ethnic Relations and Cultural Studies this research seeks to answer the following question: "What has guided the construction of the discourses of Black Brazilian youtubers?" And has as its general objective to understand the processes of discourse construction of black people who are Brazilian youtubers, between the years 2015-2020. The qualitative approach study adopted a set of methods and procedures and proposes the use of the culture circuit, along with digital ethnography, to make the assembly of the research object. As an analysis procedure to work the discourses employs some of the theoretical methodological assumptions of Michel Foucault already incorporating the criticisms made by Stuart Hall. Seven channels of black youtubers were selected: “Nátaly Neri - Afros e Afins”; “Gabi Oliveira-DePretas”; “Muro Pequeno”; “10Ocupados”; “Canal do Pericão”; “Etnia Brasileira” and “Fernando Holiday”, that altogether they produced 1.697 videos and posted them on the YouTube platform, during the period of analysis. All of them declare themselves black (black and brown); they are participants of the YouTube Partnership Program (they monetize with the production of content); most of them have already been invited or selected for some project on the platform; they have more than 100 thousand subscribers on the channel (two of them have more than a million) and somehow talk about racial issues in their videos. The data are analyzed by socio-historical context and themes that emerged in the field, among which I highlight: the processes of digital education and media literacy; critical racial literacy; the dispute of the category 'brown' and 'black'; lexicons with 'place of speech' and 'experience' in a logic of surveillance and punitivism; representation and tokenism; agency of anger; right to opacity; the house of men and the house of difference. Thus, by undertaking themselves and their black identities they end up generating representations about what it is to be a black person who is also a university student, artist, homosexual, digital influencer or politician, making them with lexicons and aesthetics proper to the techno-mediated public sphere. These are digital strategies for the construction of new regimes of representation that value what has been denied, but since it is about representation there are no guarantees.